Characterization and antibacterial properties of fish skin gelatin/guava leaf extract bio-composited films incorporated with catechin. (15th March 2023) - Chou, Ming-Yu; Osako, Kazufumi; Lee, Tan-Ang; Wang, Ming-Fu; Lu, Wen-Chien; Wu, Wei-Jun; Huang, Ping-Hsiu; Li, Po-Hsien; Ho, Jou-Hsuan
Abstract: In recent years, biodegradable materials (carbohydrates, proteins, and lipids) have similar properties to plastic materials, which can be decomposed and will not cause environmental pollution. Thus, they can be developed into edible films as food packaging materials; however, their manufacturing costs have increased several folds. Taiwanese tilapia ( Oreochromis mossambicus ) contains considerable gelatin, a by-product of the food processing industry, which can be made into an edible film combined with catechin and guava leaf extract as the principal polyphenol and flavonoid, respectively, with antioxidant and antibacterial activities. Therefore, this study investigates the properties of edible films combined with catechin-guava leaf extract at different ratios. Results showed that the film's thickness ranged from 0.053 to 0.068 mm. The film had a good barrier effect on UV rays. In addition, the edible film exhibited good antioxidant ability; it had more evident antibacterial activity against E. coli and S. aureus . Consequently, the catechin-guava leaf extract ratio of 30–70 had a better elongation at break and film thermal stability, indicating its great application potential. However, further development is required compared with polyvinyl chloride, particularly with regard to mechanical efficiency and transparency. Highlights: Edible films of gelatin, catechins, and guava-leaf extracts have potential application for food packaging. Catechins and guava-leaf extracts promote film elongation, antioxidant activity, and microbial resistance. The film will degrade to achieve environmental friendliness. The film can prevent UV radiation within a certain range. No microbial growth has been found on the contact surface of the edible film.